A proposed design of framework for E-Bill system for PKNS / Mohd Hanafi Samsudin - Samsudin, Mohd Hanafi (Faculty of Information Technology and Quantitative Sciences, 2005)
This thesis is about to propose design of framework for e-bill system for PKNS Shah Alam. The primary purpose of this research is to determine the willingness and readiness the entire resident of PKNS building to use the e-bill payment system rather than manual system and the second purpose is to suggest the best design of framework through Object Oriental Analysis (OOA) using Unified Modeling Language (UML) for e-bill payment for PKNS. The research began by distributing the questionnaire to 150 residents of PKNS building. The survey indicates that the entire resident is willing and ready for PKNS to make the online payment. The survey also states that are many weakness and problem occurring in the current manual system. It is concluded that manual system is not effective and PKNS should have other alternative system. The best recommendation is PKNS make the online payment through Maybank2u.com because most of the residents are Maybank account holder. It is recommended that the government should update their system in order to make the system become and effective. Details information will describe on this paperwork using Unified Modeling Language (UML) and also include an example ofinterfaces ofthe Electronic Bill Payment for PKNS.